Do income inequality affect internet diffusion? Empirical evidence from night light data - Fan, Jianshuang; Wang, Yuanjia; Cai, Sicheng; Feng, Qiongfang (Frontiers in Public Health, 2025)
BackgroundPromoting the application of the Internet and information technology has become an inevitable choice if a country is to achieve the country’s goal of high-quality economic development. Rising income inequality may have a dampening effect on Internet diffusion and exacerbate the digital divide. However, the amount of literature on related issues is scant.MethodsThis paper uses night light data to measure the Gini coefficients in China, and thereby to gauge the level of income inequality. Eventually, a panel data set covering 30 provinces and 272 prefecture-level cities in China from 2005 to 2020 is obtained.ResultsBased on this data set, the baseline regression results suggest that income inequality significantly inhibits Internet diffusion. The threshold regression results suggest that with the improvement of regional economic level, as well as the level of residents’ social capital and human capital, the inhibitory effect of regional income inequality on Internet consumption is weakening. The results of the heterogeneity test show that the effects on Internet diffusion in the mid-western and non-innovative cities are stronger than in the eastern and innovative cities. The results of the mechanism test show that income inequality has a negative effect on Internet diffusion through the economic suppressive effect, education crowding-out effect, and class solidification effect.ConclusionIncome inequality significantly inhibits Internet diffusion. This paper provides theoretical insights and decision-making references for effectively promoting Internet diffusion from the perspective of income inequality.